Relationship between physical activity level and plantar sensitivity, balance in postmenopausal women - Tunç, Sümeyye; Atılgan, Esra; Altuntaş, Şükriye Leyla (Taylor and Francis, 2022)
This research was planned to investigate the relationship between physical activity level and plantar sensitivity, static and dynamic balance in postmenopausal women. Forty women between the ages of 50 and 65, who had not had a menstrual period for at least 12 months, and who had undergone menopause due to hormonal, surgical or natural means were involved in the research. International Physical Activity Questionnaires Short Form (IPAQ-SF) was used to assess the level of physical activity. Light touch pressure threshold on soles of the individuals and two-point discrimination sense were evaluated bilaterally from 6 different regions of the sole of the foot. Single leg and tandem stance tests were used for static balance assessment. Dynamic balance was evaluated with Berg Balance Scale (BBS) and Timed Up and Go Test (TUG). As a result of the statistical analysis, a negative correlation was found between the total physical activity level of the participants and the light touch pressure of the right big toe. There was a significant negative correlation between total physical activity level and left big toe, and the 1st and 5th metatarsal heads of the left foot. A significant negative correlation between total physical activity level and TUG test was detected. However, no significant difference between total physical activity and BBS, static balance tests was found. As a result of this research, it was concluded that the level of physical activity affects the light touch sense of big toes of both feet, and the 1st and 5th metatarsal heads of left foot. During this study, it was seen that if total physical activity level decreases, then the score of TUG can increase. Physical activity level and related factors should be examined with a larger number of samples.
Keywords: Physical Activity; Plantar Plate; Postmenopause; Postural Balance; Sensation